EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTU MEDIA AUDIO-VISUAL DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI SEGIEMPAT - Wicaksono, Setiawan; Kusmayadi, Tri Atmojo; Sujadi, Imam (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2014)
Abstract. The objective of this research was to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the mathematical communication of the students. The learning models compared were the cooperative learning model of the TGT type with audio-visual media, the cooperative learning model of the TGT type, and the direct learning model. This research was the quasi experimental. Its population was all of the students in Grade VII of State Junior Secondary Schools of Pati regency in Academic Year 2013/2014. The taken samples used technique stratified cluster random samples consisted of 283 students, consisted 3 class, namely 97 students in Experimental Class I, 94 students in Experimental Class II, and 92 students in Control Class. The instruments to gather the data were test of achievement in Mathematics on the learning material of Quadrangle, and test of mathematical communication. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalanced cells. The results of the research were as follows: 1) The TGT type with audio-visual media results in a better learning achievement than the TGT type and the direct learning model, and the TGT provided a better learning achievement of direct learning model, 2) The students with the high mathematical communication was a better learning achievement than those with the moderate and low mathematical communication, while the students with moderate mathematical communication was the same learning achievement as those with the low mathematical communication, 3) a) In the students with the high mathematical communication, the TGT type with audio-visual media results in the same learning achievement as the cooperative learning model of the TGT type, the TGT type with audio-visual media or the TGT type results in a better learning achievement than the direct learning model, 3) b) the category of moderate and low mathematical communication, the TGT type with audio-visual media provided equal learning performance both with models the TGT type and direct learning model, 4) a) In the TGT type with audio-visual media, students who was a high mathematical communication was the same learning achievement as those with the moderate mathematical communication, the students with the moderate mathematical communication was the same learning achievement as those with the low mathematical communication, and students who with the high mathematical communication was a better learning achievement than those with the low mathematical communication, 4) b) In the TGT type, students with the high mathematical communication was a better learning achievement than those with the moderate or low mathematical communication, and students with the moderate mathematical communication was the same learning achievement as those with the low mathematical communication, 4) c) In the direct learning model, students with the high mathematical communication was the same learning achievement as those with the moderate or low mathematical communication.Keywords: TGT, audio-visual media, and mathematical communication